High-altitude mountain telemedicine. (February 2022) - Martinelli, Massimo; Moroni, Davide; Bastiani, Luca; Mrakic-Sposta, Simona; Giardini, Guido; Pratali, Lorenza
Introduction: An innovative teleconsultation platform has been designed, developed and validated between summer 2017 and winter 2018, in five mountain huts and in three remote outpatient clinical centres of the Italian region Valle d'Aosta of the Mont Blanc massif area. Methods: An ad-hoc videoconference system was developed within the framework of the e-Rés@MONT (Interreg ALCOTRA) European project, to tackle general health problems and high-altitude diseases (such as acute mountain sickness, high-altitude pulmonary and cerebral oedema). The system allows for contacting physicians at the main hospital in Aosta to perform a specific diagnosis and to give specific advice and therapy to the patients in an extreme environment out-hospital setting. At an altitude between 1500–3500 m, five trained nurses performed clinical evaluations (anamnesis, blood pressure, heart rate, oxygen saturation), electrocardiographic and echography monitoring on both tourists and residents as necessary; all of the collected data were sent to the physicians in Aosta. Results: A total of 702 teleconsultation cases were performed: 333 dismissed (47%), 356 observed (51%) and 13 immediate interventions (2%). In 30 cases the physicians decided there was no need for helicopter and ambulance rescue intervention and hospital admissions. The main physiological measures, the classified pathologies, the severe cases and the cost savings are described in this article. Discussion: The e-Rés@MONT teleconsultation platform has been discussed in terms of treated cases, feasibility, proactivity in reducing complexities, direct and indirect advantages, and diagnostics help; moreover, general and specific pros and cons have been debated, and future steps have been exposed.